2017
DOI: 10.1007/s10439-017-1802-z
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Muscle Synergies During Walking Along Rectilinear and Curvilinear Trajectories in Humans

Abstract: The aim of this study was to develop a methodology based on muscle synergies to investigate whether rectilinear and curvilinear walking shared the same neuro-motor organization, and how this organization was fine-tuned by the walking condition. Thirteen healthy subjects walked on rectilinear and curvilinear paths. Electromyographic data from thirteen back and lower-limb muscles were acquired, together with kinematic data using inertial sensors. Four macroscopically invariant muscle synergies, extracted through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 45 publications
4
35
0
Order By: Relevance
“…In PWHA, the limb with the highest score on the HJHS was selected. In the control group (CG), the dominant limb was assessed, which was determined by asking the subjects which leg they would use to kick a ball …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In PWHA, the limb with the highest score on the HJHS was selected. In the control group (CG), the dominant limb was assessed, which was determined by asking the subjects which leg they would use to kick a ball …”
Section: Methodsmentioning
confidence: 99%
“…In the control group (CG), the dominant limb was assessed, which was determined by asking the subjects which leg they would use to kick a ball. 22 After shaving and cleaning the skin with alcohol, surface electrodes (Ag-AgCl, Kendall H124SG) were placed (interelectrode spacing 2 cm) on the following muscles according to SENIAM guidelines 23…”
Section: Data Acquisitionmentioning
confidence: 99%
“…A muscle synergy is a functional group of muscles simultaneously contracting during a motor task [13]. Muscle synergy analysis has been applied both in healthy controls and neurological patients for different motor tasks, especially for walking [6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ting and Macpherson found that four muscle synergies in cats could reproduce multiple muscle activation patterns to keep balance under perturbations from different directions [13]. In particular, muscle synergy in human walking had been explored extensively [14][15][16][17][18][19]. Tang et al compared the gait muscle synergies of cerebral palsy (CP) children, and typically developed children and adults, and found that the abnormalities of muscle synergy in CP children could reflect their motor dysfunction and even the physiological change in their nervous system [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al compared the gait muscle synergies of cerebral palsy (CP) children, and typically developed children and adults, and found that the abnormalities of muscle synergy in CP children could reflect their motor dysfunction and even the physiological change in their nervous system [18]. Chia et al found that rectilinear walking and curvilinear walking shared the same muscle synergies, but a fine-tuning in muscle synergies was introduced during curvilinear conditions, adapting the kinematic strategy to the new biomechanical needs [19].…”
Section: Introductionmentioning
confidence: 99%